2018
DOI: 10.1002/cphc.201701027
|View full text |Cite
|
Sign up to set email alerts
|

Improving HSAPO‐34 Methanol‐to‐Olefin Turnover Capacity by Seeding the Hydrocarbon Pool

Abstract: Seeding the hydrocarbon pool before exposure to methanol ensures the presence of active olefinic and aromatic chain carriers in the HSAPO-34 cavity before the first methanol-to-olefin turnover. The primordial hydrocarbon pool enables the introduction, at low turnover numbers, of chain propagation steps that compete with methanol transfer dehydrogenation-mediated chain termination steps, thereby increasing the fraction of converted methanol used for productive turnovers during methanol-to-olefin catalysis over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 26 publications
(49 reference statements)
0
7
0
Order By: Relevance
“…Recent investigations indicated that formaldehydeformed through disproportionation of methanol during direct C-C bond formationcauses catalyst deactivation via interaction with aromatic molecules resulting in the formation of polycondensed aromatics. 55 Besides, formaldehyde formation is accompanied with the production of CH4. 56 It thus becomes clear that in order to achieve better catalyst stability and selectivity, the induction period should be re-engineered to avoid formaldehyde formation.…”
Section: Towards Improved Selectivity In Mthmentioning
confidence: 99%
“…Recent investigations indicated that formaldehydeformed through disproportionation of methanol during direct C-C bond formationcauses catalyst deactivation via interaction with aromatic molecules resulting in the formation of polycondensed aromatics. 55 Besides, formaldehyde formation is accompanied with the production of CH4. 56 It thus becomes clear that in order to achieve better catalyst stability and selectivity, the induction period should be re-engineered to avoid formaldehyde formation.…”
Section: Towards Improved Selectivity In Mthmentioning
confidence: 99%
“…The accumulation of "coke" (including PAHs) with reaction progress can gradually enhance ethene selectivity on SAPO-34 31,32 .…”
Section: Choosing Industrially Important Mto As a Model Reactionmentioning
confidence: 99%
“…Unraveling the reaction mechanism is a big challenge in MTO conversion. For the MTO process, the dual‐cycle hydrocarbon pool schematic comprised of olefinic and aromatic methylation cycles has been well accepted , . In the induction period, the methanol was generated polymethylbenzene compounds, which are the most important active intermediate in the methanol conversion process .…”
Section: Resultsmentioning
confidence: 99%